Samapta Sat Patrol Unit R2 Patrol Efforts in Preventing the Crime of Theft with Weights in the Jurisdiction Area of the Tuban Police - Abas, Mohammad Alfin (Advances in Police Science Research Journal, 2024)
This research aims to describe the organizational resource conditions supporting R2 patrol activities and to explain the implementation of R2 patrols by the Samapta Unit of Tuban Police Resort in efforts to prevent aggravated theft crimes. A qualitative descriptive approach was used with data collection through interviews, observations, and document studies. One of the factors influencing the increase in aggravated theft cases in Tuban Regency is personnel shortages. From the research results using the POAC and 6M management theories, it can be concluded that lack of supervision, AAP provision, personnel shortages, and material shortages such as fuel are some of the obstacles faced by the Samapta Unit patrols of Tuban Police Resort, resulting in ineffective patrols. Therefore, efforts undertaken by the Samapta Unit patrols of Tuban Police Resort include creating SOPs aimed at guiding the determination of patrol time and location, engaging in dialogues with the community to convey security messages and receive reports from the community, and implementing a reward and punishment system.